Will exercise advice be sufficient for treatment of young adults With prehypertension and hypertension? A systematic review and meta-analysis. - Williamson, W; Foster, C; Reid, H; Kelly, P; Lewandowski, A; Boardman, H; Roberts, N; McCartney, D; Huckstep, O; Newton, J; Dawes, H; Gerry, S; et al. (American Heart Association, 2016)
Previous studies report benefits of exercise for blood pressure control in middle age and older adults, but longer-term effectiveness in younger adults is not well established. We performed a systematic review and meta-analysis of published randomized control trials with meta-regression of potential effect modifiers. An information specialist completed a comprehensive search of available data sources, including studies published up to June 2015. Authors applied strict inclusion and exclusion criteria to screen 9524 titles. Eligible studies recruited younger adults with a cardiovascular risk factor (with at least 25% of cohort aged 18 to 40 years); the intervention had a defined physical activity strategy and reported blood pressure as primary or secondary outcome. Meta-analysis included 14 studies randomizing 3614 participants, mean age 42.2+/-6.3 (sd) years. At 3 to 6 months, exercise was associated with a reduction in systolic blood pressure of –4.40 mmHg (95%CI, -5.78 to -3.01) and in diastolic blood pressure of -4.17 mmHg (95%CI, -5.42 to -2.93). Intervention effect was not significantly influenced by baseline blood pressure, body weight or subsequent weight loss. Observed intervention effect was lost after 12 months follow-up with no reported benefit over control, mean difference in systolic blood pressure -1.02 mmHg (95%CI, -2.34 to 0.29) and in diastolic blood pressure –0.91 mmHg (95%CI, -1.85 to 0.02). Current exercise guidance provided to reduce blood pressure in younger adults is unlikely to benefit long-term cardiovascular risk. There is need for continued research to improve age specific strategies and recommendations for hypertension prevention and management in young adults.